Estimating Mina Jaya Niaga 11 Ship Repair (In Man-hour) using Work Breakdown Structure - Danuja Wijayanto; Taufik Fajar Nugroho; Agoes Achmad Masroeri (Jurnal Teknik ITS, 2017)
Mina Jaya Niaga fishing vessel procurement project were unsuccessful. There are 34 planned to be built but only 14 were able to be finished. Through the Minister of Maritime Affairs and Fisheries, the government intended to use the vessels again. Based on the recent survey, Mina Jaya Niaga 11 is one of the five vessels which still worthy to be repaired. The government intended to use the vessel because there is still a potency of tuna fishing in Indonesia. The demand for tuna in the market is growed as Tuna is one of the high-value marine commodity and popular in the world. An economic feasibility study is likely to be conducted to analyze whether the vessel is feasible or not. The capital expenditure, one of the components to be used for feasibility study needed to be examined. The capital expenditure in this project is the estimation cost of the ship refurbishment. Work breakdown structure in order to categorize the vessel repairing aspect is used on this paper to estimating the vessel repair cost. The result of the repair cost is only the shipyard cost and the total man-hour is about 7910 hour.